Review of Antibiotic Use Regulations in Healthcare Facilities Based on The Minister of Health Regulation No. 28 Of 2021: Literature Review - Febya Yuhendra Putri (Fox Justi : Jurnal Ilmu Hukum, 2025)
Use antibiotics that do not appropriate become factor main increasing resistance antibiotics in Indonesia. For overcome matter this, the government emit Minister of Health Regulation No. 28 of 2021 for set guidelines in rational use of antibiotics in facilities health. The purpose of study This is to review its implementation and identify the implementation of Permenkes No. 28 of 2021 in health facilities in Indonesia in an effort to control antibiotic resistance in Indonesia. The method used with review literature conducted in field national and international for five years last. Research results show that, both at home sick, health centers, and pharmacy, there is Lots challenges that stand in the way implementation regulation This. Use antibiotics without prescription, therapy that is not in accordance guidelines, and use antibiotics spectrum wide without clear indication is a number of violations found. Therefore, it is necessary to strengthen policy implementation through education, antibiotic use audits, and a One Health- based cross - sector approach to effectively control antibiotic resistance in Indonesia.